Mek1 Down Regulates Rad51 Activity during Yeast Meiosis by Phosphorylation of Hed1. - Tracy L Callender; Raphaelle Laureau; Lihong Wan; Xiangyu Chen; Rima Sandhu; Saif Laljee; Sai Zhou; Ray T Suhandynata; Evelyn Prugar; William A Gaines; YoungHo Kwon; G Valentin Börner; et al. (PLoS Genetics, 2016)
During meiosis, programmed double strand breaks (DSBs) are repaired preferentially between homologs to generate crossovers that promote proper chromosome segregation at Meiosis I. In many organisms, there are two strand exchange proteins, Rad51 and the meiosis-specific Dmc1, required for interhomolog (IH) bias. This bias requires the presence, but not the strand exchange activity of Rad51, while Dmc1 is responsible for the bulk of meiotic recombination. How these activities are regulated is less well established. In dmc1Δ mutants, Rad51 is actively inhibited, thereby resulting in prophase arrest due to unrepaired DSBs triggering the meiotic recombination checkpoint. This inhibition is dependent upon the meiosis-specific kinase Mek1 and occurs through two different mechanisms that prevent complex formation with the Rad51 accessory factor Rad54: (i) phosphorylation of Rad54 by Mek1 and (ii) binding of Rad51 by the meiosis-specific protein Hed1. An open question has been why inhibition of Mek1 affects Hed1 repression of Rad51. This work shows that Hed1 is a direct substrate of Mek1. Phosphorylation of Hed1 at threonine 40 helps suppress Rad51 activity in dmc1Δ mutants by promoting Hed1 protein stability. Rad51-mediated recombination occurring in the absence of Hed1 phosphorylation results in a significant increase in non-exchange chromosomes despite wild-type levels of crossovers, confirming previous results indicating a defect in crossover assurance. We propose that Rad51 function in meiosis is regulated in part by the coordinated phosphorylation of Rad54 and Hed1 by Mek1.